The Influence of Attractiveness, Online Customer Reviews, and Discounts on Purchase Decisions, with Perceived Enjoyment as an Intervening Variable - Renaldi, Putu Alit; Sanica, I Gede (Jurnal Manajemen Bisnis, 2024)
Technological advances bring various conveniences to society, especially in online shopping. Shopee as an e-commerce with the most users in Indonesia is an opportunity and a challenge in the very tight competition for sellers in it. To be able to compete in this perfect market, sellers must be able to apply factors that can improve purchasing decisions to compete with other sellers. This research seeks to examine purchasing decision factors mediated by Perceived Enjoyment. The sample for this research consisted of 144 active Shopee users in Indonesia. The process of gathering data involved sending out Google Form surveys with an interval scale of 1-10. Data analysis uses the Structural Equation Modeling program using the Part Lease Square method. The results of this research show that the independent variables attractiveness, online customer reviews, and discounts can have a significant and partially positive influence on Perceived Enjoyment. Attractiveness and online customer reviews can have a significant and positive influence on Purchase Decisions. This research also found that discounts did not have a direct effect on Purchase Decisions, but after being mediated through Perceived Enjoyment, significant and positive results were found. Future research is expected to add other variables to strengthen research on Purchase Decisions.